Effect of Severities and Timing of Defoliation on Root Yield and Quality of Sugar Beet (Beta vulgaris L.) at Alkadarou - Idris, Baha Eldin M.; Sulfab, Hatim A.; Eltony, Esam Eldeen M. A.; Eltyieb, Karima A.; Asha, I.; Marajan, Wael A. (European Journal of Applied Sciences, 2022)
A field experiment was conducted in winter for two successive seasons (2015-2016 and 2016-2017) at College of Agriculture Farm, University of Bahri, Sudan to investigate the effect of severities and timing of defoliation on root yield and quality of sugar beet (Beta vulgaris L.). The experimental design was Randomized Complete Block / factorial with four replicates. Three defoliation severities 0% (control) ,50%, and 100% were applied which referred to as S0, S1, and S2 respectively and four dates of defoliation 7weeks after sowing , 10weeks after sowing , 13weeks after sowing , and 16 weeks after sowing (WAS) which referred to as T1 , T2 , T3 , and T4 respectively. Results showed that 100 % defoliation decreased significantly Brix%, Pol. %, root yield t/ha, and white sugar t/ha in both seasons when compared to control. Results revealed that different treatments of defoliation time, in first season, had no significant differences on Pol. %, root yield t/ha, and white sugar t/ha; and significant differences only on Brix. % . In second season Pol. % and root yield t/ha were not significant whereas Brix. % and white sugar t/ha were significantly decreased as affected by different treatments of defoliation time. Generally, 100% defoliation at 13 WAS gave the lowest records of studied parameters in both seasons.